Analisis Kapasitas Produksi Menggunakan Metode Rough Cut Capacity Planning Pada CV Tahaki Multi Kreasi - Wirawan, Eko; Setiafindari, Widya (Sekolah Tinggi Teknologi Dumai, 2024)
CV Tahaki Multi Kreasi is a company engaged in interior, exterior and advertising. The number of requests for cabinet room products tends to fluctuate every month. In 2023, from January to December, CV Tahaki Multi Kreasi received 143 cabinet room order projects. To estimate the amount of demand, effective forecasting is needed. Forecasting uses methods namely Moving Average, Exponential Smoothing, and Trend Analysis. The most effective forecasting uses the Trend Analysis method which has the smallest forecasting error. The MAD value is 1.9005, MSE is 4.5343, and MAPE is 19.2362. The production schedule at CV Tahaki Multi Kreasi is carried out every two weeks for optimal results. Production capacity requirements are calculated using the Rough Cut Capacity Planning (RCCP) method. The RCCP method is used to determine the possibility of insufficient capacity or overload in determining production capacity.. The total capacity required in all work centers is 962 hours, while the total available capacity is 2016 hours. The analysis shows that there is no capacity shortage at each work station because the variance shows negative and the load percentage is 54.2%.